Partículas nanométricas de ferritas de ítrio - Godoi,Ricardo H. M. (1999)
Nanoparticles of yttrium iron garnet (YIG) were obtained by coprecipitation. The particles were prepared by hydrolysis in acid medium with addition of ammonia or urea, for homogeneous nucleation, at 90ºC. Different compositions and spherical morphologies were achieved by changing reactants concentrations and precipitation agent. X-ray diffractometry, transmission electron microscopy, differential thermal analysis and electrophoretic mobility were carried out on these particles to investigate the obtained phase, phase transition temperature, morphology, particle size and zeta potential, respectively.